PEMILAH SAMPAH PINTAR BERDASARKAN LOGAM DAN NONLOGAM DI KANTOR FAKULTAS TEKNIK - Reva Deddy Pradana; Desriyanti Desriyanti; Rhesma Intan Vidyastari (KOMPUTEK, 2021)
Garbage is an object or material that is no longer used by humans so that it is thrown away. Community activities that produce waste are not only the responsibility of the government, but the community must also be responsible for processing waste so that it does not have a negative impact on the surrounding environment. Garbage is one of the problems that must be considered, because waste from year to year continues to increase along with the increase in population. In order not to cause environmental pollution, waste must be processed according to the type of waste so that it is beneficial for people's lives and health. Therefore, waste must be sorted according to the type of waste to facilitate the recycling process. For the waste sorting process, it is still done conventionally, and manually, namely sorting using different methods of garbage bins based on the type of waste and sorting manually, using staff. Waste sorting that previously used the manual method was replaced with an automatic sorting system. This waste sorting system starts from the input process that comes from the proximity sensor, loadcell sensor, and ultrasonic sensor. This system uses Arduino Mega as a micro controller that functions as a data processing center in the sorting system. The results obtained are that the proximity sensor can detect the type of waste and send data to the Arduino to determine where the servo motor will move to move the garbage according to its type. The weight of the garbage in the container is measured with a loadcell sensor to detect how much garbage weighs. Ultrasonic sensors can measure the amount of waste in the container. Users can see the status of the container on the LCD attached to this tool.